PENGARUH BAURAN PEMASARAN DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA SEMOGA SUKSES CELL PEKANBARU) - Hafifa Husna; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the effect of the marketing mix and the quality of service on purchasing decisions (study in the semoga sukses cell Pekanbaru) partially and simultaneously. Marketing mix and service quality as independent variables () while purchasing decisions as the dependent variable (Y). this research was conducted at semoga sukses cell Pekanbaru which is located at Jalan Lembaga Permasyarakatan No. 15 B Pekanbaru. In this study the methodology used was descriptive and quantitative with the SPSS program, where the sample in this study were customers of semoga sukses cell Pekanbaru many as 100 respondents. To determine the sample using the Slovin formula, the sampling technique with accidental sampling. Techniques for collecting data through questionnaires. From data analysis which includes validity test, reliability test, classic assumption test, simple linear analysis, multiple linear analysis, determination analysis and significance test by testing t test (partial) and f test (simultaneous). The results of this study indicate that the results of testing the first t test hypothesis, marketing mix of purchasing decisions is tarithmetic (15,089) > ttabel  (1,984) means that the marketing mix has a significant effect on purchasing decisions. Second, the quality of service to purchasing decisions is tarithmetic (10,817) > ttabel  (1,984), which means that service quality has a significant effect on purchasing decisions. Test results F marketing mix and service quality on purchasing decisions are (163,044) >  (3,09).  This means that the marketing mix and service quality simultaneously have a significant effect on purchasing decisions.  Keywords: Marketing Mix, Service Quality, Purchase Decision